Characteristics of Acute Nongonococcal Urethritis in Men Differ by Sexual Preference - Rane, Vinita S. (American Society for Microbiology, 2014)
Nongonococcal urethritis (NGU) is a common clinical syndrome, but no etiological agent is identified in a significant proportion of cases. Whether the spectrum of pathogens differs between heterosexual men (MSW) and men who have sex with men (MSM) is largely unstudied but of considerable clinical relevance. A retrospective review was done using the electronic medical record database of Melbourne Sexual Health Centre, Australia. Cases were first presentations of symptomatic acute NGU with ≥5 polymorphonuclear leukocytes (PMNL)/high-powered field (HPF) on urethral Gram stain between January 2006 and December 2011. First-stream urine was tested for Chlamydia trachomatis and Mycoplasma genitalium by PCR. Demographic, laboratory, and behavioral characteristics of cases were examined by univariate and multivariable analyses. Of 1,295 first presentations of acute NGU, 401 (32%; 95% confidence interval [CI] of 29 to 34%) had C. trachomatis and 134 (11%; 95% CI of 9 to 13%) had M. genitalium detected. MSM with acute NGU were less likely to have C. trachomatis (adjusted odds ratio [AOR] = 0.4; 95% CI of 0.3 to 0.6) or M. genitalium (AOR = 0.5; 95% CI of 0.3 to 0.8) and more likely to have idiopathic NGU (AOR = 2.4; 95% CI of 1.8 to 3.3), to report 100% condom use for anal/vaginal sex (AOR = 3.6; 95% CI of 2.7 to 5.0), or to have engaged in sexual activities other than anal/vaginal sex (AOR = 8.0; 95% CI of 3.6 to 17.8). Even when C. trachomatis or M. genitalium was detected, MSM were more likely than MSW to report consistent condom use (OR = 4.7; 95% CI of 2.6 to 8.3). MSM with acute NGU are less likely to have the established bacterial sexually transmitted infections (STIs) and more likely to report protected anal sex or sexual activity other than anal sex prior to symptom onset than MSW. These data suggest that the etiologic spectrum of pathogens differs between MSM and MSW in acute NGU and that relatively low-risk practices are capable of inducing acute NGU.